Micro milling of NiTi shape memory alloy and determination of critical chip thickness [Şekil hafizali NiTi alaşiminin mikro frezelenmesi ve kritik talaş kalinliǧinin belirlenmesi] - (:unkn) unknown (Gazi Universitesi Muhendislik-Mimarlik, 2019)
Shape memory alloys (SMA) are widely used in the biomedical field due to their unique properties. Among these alloys, NiTi alloys are the most widely used. Machining process is one of the techniques to form these materials. If the NiTi alloys are mechanically forced to be cut, the crystal lattice structure can change and thus phase transformation can occur. Phase transformation naturally affects cutting forces and tool life. In this study, the milling of NiTi alloy under micro-cutting conditions was investigated experimentally. For this, an experimental setup with high precision and cutting at high cutting speeds was used. A wide range of depth of cut and feed per tooth were used in the study. Thefore, it was tried to determine the chip thickness which is critical in milling NiTi alloy. Output parameters obtained at the end of the study; cutting forces, surface roughness and burr width. The obtained results show that for NiTi SHA, the critical chip thickness is 0.5μm. The critical chip thickness corresponds to about 33% of the radius of the cutting edge. However, depending on the increased cutting speed, both the cutting forces and the burr widths increases. © 2019 Gazi Universitesi Muhendislik-Mimarlik. All rights reserved.
Keywords: Critical chip thickness; Micro milling; NiTi shape memory alloy; Surface roughness